Strategi Pendidikan Agama Islam dalam Mengatasi Krisis Moral Dikalangan Remaja - Arrum Agustina; Agnes Tri Muryati; Evita Nadia; Eza Dwi Lestari (Yayasan Darusssalam Bengkulu, 2025)
The moral crisis among teenagers is one of the biggest challenges in modern society, triggered by technological developments, the influence of foreign culture, and shifts in social values. This phenomenon is reflected in various deviant behaviors, such as increasing juvenile delinquency, uncontrolled consumer behavior, promiscuity, and decreased respect for parents and authority. In the midst of this situation, Islamic Religious Education (PAI) plays an important role in shaping the character and morals of the younger generation through noble religious values. This article focuses on strategies that can be implemented in PAI to face and overcome moral crises among teenagers. The strategies discussed include strengthening understanding and internalizing the values of Islamic teachings, providing good role models (uswah hasanah) from teachers, parents and community figures, as well as using social media as a means of disseminating moral messages that are relevant to the lives of teenagers. Apart from that, this article also emphasizes the importance of a holistic approach that involves family, school and social environment in the character formation process. Good collaboration between schools and parents through character development programs is also identified as a key factor in supporting the effectiveness of PAI. By implementing these strategies systematically, it is hoped that teenagers can avoid moral crises and grow into individuals with noble character, integrity, and able to face the challenges of the times armed with strong Islamic values. Key words: Islamic religious education, moral crisis, teenagers, educational strategies, character formation.